Semiotics Study Of Warning Symbol For Common Reactions Caused By Cow’s Milk Protein Allergy (CMPA) - Adinan, Nur Intan Dayana; Abd Jamil, Azhar (2016)
Cow’s milk protein allergy or known as CMPA among healthcare professionals, is one of the most common allergy reactions among infants and children in Malaysia. It is different from lactose intolerance. It usually happens to infants aged 6 months and below and to children under 3 years old. However, no data or statistics have been officially recorded on cow’s milk protein allergy in Malaysia. Not all mothers are capable of breastfeeding their child even though a mother’s milk is the best to nourish said child. Thus, mothers are given the choice of formula milk, to replace their own milk. There are many brands available in the market with regards to infant milk formula but there are three types of milk formula for babies; the common one being cow milk base formula. However, there are infants or babies who are hypersensitive to cow’s milk protein or casein. Warning signs to alert the parents about CMPA is imperative. In this study, the researcher studied the best possible warning sign, which is in pictorial visual so that it can be easily recognised by the public, with the difference in background and lifestyle. Eight categories or common symptoms of pictograms designs have been created to discern the most suitable pictogram as the ultimate warning sign. The result of the study suggests that the pictograms has to be clear and can be understood by the public coming from different backgrounds. The choices of warning signs and warning statements also play a big role in creating the warning sign. It is hoped that the study can contribute to the consumers and public especially for those with children suffering from CMPA